RSM-based sensitivity analysis of hybrid nanofluid in an enclosure filled with non-Darcy porous medium by using LBM method - Venkatadri, Kothuru; Öztop, Hakan Fehmi Fehmi; Prasad, Vallampati Ramachandra; Parthiban, Settu; Beg, Anwar Osman (Taylor & Francis Inc, 2024)
The emphasis of this study is the numerical analysis via D2Q9-based Lattice Boltzmann Method of free convection MHD non-Darcy flow in hybrid nanofluid (TiO2/Cu-water) occupying a differentially heated square enclosure. A key novelty of the work is the inclusion of a response surface methodology (RSM)-based sensitivity analysis. The current investigation has been done considering the variation in Rayleigh number (10(3) <= Ra <= 10(6)), Darcy number (0.0001 <= Da <= 0.1), and Hartmann number (0 <= Ha <= 50). From RSM, high Darcy parameter, low volumetric fraction, and low Hartmann number are identified as the optimum functioning conditions for heat transfer rates.
Keywords: Heat transfer; hybrid nanofluid; lattice Boltzmann method; magnetic field; porous medium; sensitivity analysis